Association of plasma neopterin with risk of an inpatient hospital diagnosis of atrial fibrillation: results from two prospective cohort studies. (24th March 2018) - Zuo, H.; Nygård, O.; Ueland, P. M.; Vollset, S. E.; Svingen, G. F. T.; Pedersen, E. R.; Midttun, Ø.; Meyer, K.; Nordrehaug, J. E.; Nilsen, D. W. T.; Tell, G. S.
Abstract: Background: Link between inflammation and atrial fibrillation (AF) has been increasingly recognized. Neopterin, a biomarker of cellular immune activation, may be associated with incident AF. Objective: To investigate the association between plasma neopterin levels and risk of an inpatient hospital diagnosis of AF, and to evaluate a joint association of neopterin and a nonspecific inflammatory marker C‐reactive protein (CRP) in two prospective cohorts. Methods: We performed a prospective analysis from a community‐based cohort (the Hordaland Health Study (HUSK), n = 6891), and validated the findings in a cohort of patients with suspected stable angina pectoris (the Western Norway Coronary Angiography Cohort (WECAC), n = 2022). Results: In both cohorts, higher plasma levels of neopterin were associated with an increased risk of incident AF after adjustment for age, sex, body mass index, current smoking, diabetes, hypertension and renal function. The multivariable‐adjusted hazard ratio (HR) (95% CI) per one SD increment of log‐transformed neopterin was 1.20 (1.10–1.32) in HUSK and 1.26 (1.09–1.44) in WECAC. Additional adjustment for CRP did not materially affect the risk association for neopterin. The highest risk of AF was found among individuals with both neopterin and CRP levels above the median (HR: 1.54; 95% CI: 1.16–2.05 in HUSK and HR: 1.67; 95% CI: 1.11–2.52 in WECAC). Conclusions: Our findings indicate an association of plasma neopterin with risk of an inpatient hospital diagnosis of AF, which remains after adjustment for traditional risk factors as well as for CRP. This study highlights a role of cellular immune activation, in addition to inflammation, in AF pathogenesis. Abstract : Click here to view the Editorial Comment by J. C. Kaski